2022
DOI: 10.3390/molecules27175579
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile, Antioxidant, Anti-Enzymatic and Cytotoxic Activity of the Fruits and Roots of Eleutherococcus senticosus (Rupr. et Maxim.) Maxim

Abstract: Eleutherococcus senticosus (Rupr. et Maxim.) Maxim. is well-known for its adaptogenic properties in traditional Eastern medicine. It has been categorized as an endangered species due to the over-exploitation of the roots. As a result, alternatives must be found, including the usage of renewable aerial parts such as fruits. The goal of this research was to determine the phenolic compounds and the enzymatic, antioxidant, and cytotoxic activities of the intractum gained from the E. senticosus fruits and the mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The According to the Pharmacopeia requirements [8,9,12,16,18,19,33,34] the medicinal raw material of E. senticosus is the root. Our literature data [20,42] has shown that the leaves of E. senticosus are also a good source of BAC.…”
Section: Resultsmentioning
confidence: 99%
“…The According to the Pharmacopeia requirements [8,9,12,16,18,19,33,34] the medicinal raw material of E. senticosus is the root. Our literature data [20,42] has shown that the leaves of E. senticosus are also a good source of BAC.…”
Section: Resultsmentioning
confidence: 99%
“…Diversely, a paucity of data exists concerning the effects induced by the other two extracts composing the blend, i.e., E. senticosus and E. purpurea , on glioma or GBM cell lines. Nevertheless, the immunomodulatory action and antioxidant properties of both E. senticosus and E. purpurea have been recorded [ 56 , 57 , 58 , 59 , 60 , 61 ], revealing their ability to activate an ancillary onco-suppression mechanism and to reduce the side effects of chemotherapy [ 62 ]. Therefore, although the current data are preliminary and further investigations could be carried out to better highlight possible synergistic effects of the proposed treatments, evaluating potential in vitro antitumor activity after combined treatments using the proposed chemotherapeutic and phyto-mycotherapeutic treatments (e.g., through the use of Chou and Talalay or similar formalism), as well as the possible in vivo metabolism, immunomodulatory effects, and blood–brain barrier permeability, the present investigation seems to support the use of this phyto-micotherapeutic preparation as a promising adjuvant in the field of integrative oncology, also paving the way to further in-depth studies devoted to clarifying the cellular/molecular mechanisms induced by each natural extract composing Ganostile .…”
Section: Discussionmentioning
confidence: 99%
“…Lignans (eleutherosides), flavonoids (rutoside, hyperoside, prunin, isoquercetin, kaempferol glycosides), hydroxycinnamic (chlorogenic, ferulic, rosmarinic, caffeic), and hydroxybenzoic (protocatechuic, vanillic, gallic) acids [57][58][59][60] Eucalyptus spp. Flavonoids (quercetin, rutin, catechin) and phenolic acids (gallic, chlorogenic, and ellagic) [61] Hypericum perforatum L.…”
Section: Medicinal Plantmentioning
confidence: 99%